2012
DOI: 10.1021/jm300383k
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Antiviral Evaluation of Purine-β-lactam and Purine-aminopropanol Hybrids

Abstract: Purine-β-lactam chimera were prepared as a novel class of hybrid systems through N-alkylation of 6-benzylamino- or 6-benzyloxypurine with (ω-haloalkyl)-β-lactams, followed by reductive ring opening of the β-lactam ring by LiEt(3)BH to provide an entry into the class of purine-aminopropanol hybrids. Both new types of hybrid systems were assessed for their antiviral activity and cytotoxicity, resulting in the identification of eight purine-β-lactam hybrids and two purine-aminopropanol hybrids as promising lead s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 52 publications
0
40
0
2
Order By: Relevance
“…MMV688352 ( 638 ) was developed as part of a wider study, which sought to identify purine‐containing β‐lactam antivirals, where it showed encouraging activity against human respiratory syncytial virus, coxsackie B virus, and chikungunya virus, but was inactive against dengue . Chang et al.…”
Section: Dengue Virusmentioning
confidence: 99%
“…MMV688352 ( 638 ) was developed as part of a wider study, which sought to identify purine‐containing β‐lactam antivirals, where it showed encouraging activity against human respiratory syncytial virus, coxsackie B virus, and chikungunya virus, but was inactive against dengue . Chang et al.…”
Section: Dengue Virusmentioning
confidence: 99%
“…10 Arbidol was found to have an IC50 of 12.2 µM. In 2012, D'Hooghe et al 11 reported that two purine-β-lactam hybrids possess anti-CHIKV activity with EC50 of 17.11 and 13.01 µM, respectively, and selectivity 3 indices (SIs) of >5.75 and >4, respectively. Additionally, purine-aminopropanol exhibits an EC50 of 11.51 µM with an SI > 6.15.…”
Section: Introductionmentioning
confidence: 99%
“…23) from Anacolosa pervilleana, namely Madagascan plant. Purine-based inhibitors D' Hooghe et al 100 reported the design and synthesis of a novel series of purine-b-lactam hybrids and purine-aminopropanol hybrids and their potential antiviral activities. 77,99 2.8.7.…”
Section: Lupenone and B-amyronementioning
confidence: 99%
“…77,99 2.8.7. 77,100 a All data are mean values ± standard deviation for at least three independent experiments. In total, nine different viruses were included in this study.…”
Section: Lupenone and B-amyronementioning
confidence: 99%